QUR'ANIC INSIGHTS ON RELIGIOUS MODERATION AND ITS RELEVANCE TO RELIGIOUS HARMONY IN INDONESIA - Andri Sutrisno; M. Rama Haqiqi; Baiq Melisa Roza; Muhammad Masruri Dalail (Universitas Muhammadiyah Surakarta, 2023)
Indonesia is a plural country consisting of various religions, tribes, races, cultures, and languages, from all of that, many of us will encounter various kinds of problems, especially young people today or often known as the millennial era. At this time the most we will encounter is the issue of Religious moderation or about how tolerance between religious people. Therefore, the emergence of religious moderation insights in the Islamic perspective can provide space for us both in studying and understanding how religious moderation should be in the Qur'an. Not only that, the important role in the emergence of various problems in the religious field makes it an attraction or study material that should be resolved. The Qur'an provides answers to all the problems we face, be it religious, cultural, or even more suggestive of politics which is all set out in the Qur'an. We only need to understand and study, especially with the problem that has always been a problem, namely moderation and tolerance in the perspective of Islam or the Qur'an.